An integrated supplier selection approach incorporating decision maker's risk attitude using ANN, AHP and TOPSIS methods. Issue 9 (11th October 2019) - Yu, Chunxia; Zou, Zhiqin; Shao, Yifan; Zhang, Fengli
Abstract : Purpose: The purpose of this paper is to develop a novel integrated supplier selection approach incorporating decision maker's risk attitude using the artificial neural network (ANN), analytic hierarchy process (AHP) and technique for order of preference by similarity to ideal solution (TOPSIS) methods. Design/methodology/approach: In the proposed approach, the ANN model is used to classify decision maker's risk attitude; the fuzzy AHP method is used to determine the relative weights of evaluation criteria; and the fuzzy TOPSIS method is used to evaluate ratings of suppliers. Finally, experiments are conducted to verify the feasibility and efficiency of the proposed integrated approach. Findings: Experiments results show that the proposed integrated approach is effective and efficient to help decision makers to select suitable suppliers according to their risk attitudes. Originality/value: The aim of this paper is to develop a novel integrated supplier selection approach incorporating decision maker's risk attitude using the ANN, AHP and TOPSIS methods. The decision maker's risk attitude toward procurement transaction is originally considered in supplier selection process.